Sun safety measures among construction workers in Britain - Madgwick, Paul; Houdmont, Jonathan; Randall, Raymond (Oxford Journals, 2011)
Background: Relative to other occupational groups in Britain, construction workers have a high incidence of skin cancer attributable to sun exposure. The importance of sun safety measures to minimize the risk of skin cancer is recognized in the literature; however, little is known about the factors associated with their use by construction workers. Knowledge in this area could help inform interventions to encourage sun safety behaviour within the sector. Aims: To investigate socio-demographic and occupational characteristics associated with the use of sun safety measures among construction workers in Britain. Methods: Data collection was by means of a self-administered questionnaire, which was sent to 360 construction workers. Information collected included socio-demographic and occupational characteristics and the use of sun safety measures. Results: Participants worked outdoors for an average of 6.6 h/day. Three specific sun safety measures were used by the majority of respondents. Logistic regression analyses showed that certain socio-demographic and occupational factors were associated with the use of sun safety measures. In particular, receipt of sun safety training was positively associated with the wearing of long sleeved, loose fitting tops and trousers (OR, 1.69; 95% CI, 1.02–2.80) and sunglasses (OR, 1.85; 95% CI, 1.10–3.13). Conclusions: The results highlight the importance of employer-led sun safety interventions in the British construction industry. Interventions that take account of demographic and occupational characteristics are likely to have a positive impact in terms of improving workers’ use of sun safety measures.